Disposition of Islamic Education Against the Principles of Democracy - Salis Irvan Fuadi; Robingun Suyud El Syam (Program Pascasarjana Universitas Ibrahimy, 2023)
The development of education in society requires a lively atmosphere so that good results can be obtained. Democratic education is thought to be the solution. Through a literature search, the research concludes: that the conception of Islam brought by the Messenger of Allah is something that does not conflict with democracy. However, the principles he offers have their own conception of democracy, whose conception is more beautiful than the conception of Western scientists' ideas. As for the principles of Islamic education which is the nature of Islamic democracy, it can be found in various principles, namely the tradition of free and right thinking (ijtihad); equality (al-musawwa), deliberation (shura), loyalty (bai'at); and parliament (majlis). In its implementation, the principles of democracy must be based on the principles of justice ('adl), truth (haqq), and freedom (hurriyyah). These principles can be practiced in educational activities so that Islamic education democracy is the implementation of Islamic democratic principles in Islamic education